10. KERJA SAMA INDONESIA DAN INTERNATIONAL LABOUR ORGANIZATION DALAM MENANGANI KASUS PEKERJA ANAK SEKTOR BERBAHAYA PERIODE 2010-2013 - Gala Panuga Azis; Hermini Susiatiningsih; Satwika Paramasatya (Journal of International Relations Diponegoro, 2016)
Hazardous Child Labor is an important issue, because it violates the Internationalregulations and Human Rights. Hazardous Child Labor is divided into 4 types, namely:Debt bondage, Utilize a child to engage in prostitution and pornography, Work relating tonarcotics and psychotropic drugs, Work that threatens the health, safety, or morals ofchildren. Children have the potential to be developed in order to participate actively in thedevelopment, in the future. Thus, International cooperation needs to be done so that theelimination of Hazardous child Labour can be met because The existence of theinternational community is increasingly plural increasing interdependence amonginternational actors (Baylis, Smith & Owens). In this research collaboration undertakenby the ILO and Indonesia, as for the purpose of the study, is to examine the role ofIndonesia and ILO in terms of addressing the case of Hazardous Child Labor. To addressthis problem, the research method used is a qualitative method, with the type ofdescriptive analytical research, through research techniques literature and interviews. Theresults of this study, revealed that the cooperation between the ILO and Indonesia in2010-2013 in the removal of Hazardous Child Labor, is to implementing programs,namely: Combating Child Labour through Education, Preparing Youth Facing Transitionfrom School to Work and Entering the World of Work, Combating Child Labour throughTraining skills for children Achieve Minimum Working Age. The programshavedecreasedthe numbers of child workers in Indonesia, but still, there are other factorsinhibiting and motivating the elimination of hazardous child labor.